THE DEBT OF PROTOZOOLOGY TO GARY N CALKINS 1869 1943 - BELTRAN, ENRIQUE (Los Alamos Laboratorio, Nuevo México, 1947)
Twenty works on Mexican natural history are discussed, especially those dealing with pre-Spanish natural history, botany and medicine in ancient Mexico
REV SOC MEX HIST NAT
Keywords: DEBT, PROTOZOOLOGY, GARY N CALKINS 18691943; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); PROTOZOOLOGIA